Nurses' Caring Behavior in Hospital: A Literature Review - Samsualam Samsualam; Al Ihksan Agus; Haeril Amir (Universitas STRADA Indonesia, 2021)
The review was carried out using the PRISMA and PICO methods based on the search results of the BMC, IJCS, IJRPH, Science Direct and Wiley Online databases, with the keyword